2002
DOI: 10.1017/s0033291701005153
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric, demographic and personality characteristics of elderly sex offenders

Abstract: Elderly sex offenders and non-sex-offenders have similar prevalence rates of mental illness. However, elderly sex offenders have increased schizoid, obsessive-compulsive, and avoidant personality traits, supporting the view that sex offending in the elderly is associated more with personality factors than mental illness or organic brain disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 24 publications
4
39
2
5
Order By: Relevance
“…Clark and Mezey [57] found low rates of mental illness including dementia in a group of 13 offenders. Fazel et al (2002) compared around 100 elderly sexual offenders to a similar comparison group and found a surprising low dementia rate of 1 %, suggesting offending was less related to cognition and more to personality factors [58]. Similarly, in comparing 50 elderly sexual and non-sexual offenders, again frontal lobe dysfunction was apparently normal [59].…”
Section: Aging and Sexual Offendingmentioning
confidence: 98%
“…Clark and Mezey [57] found low rates of mental illness including dementia in a group of 13 offenders. Fazel et al (2002) compared around 100 elderly sexual offenders to a similar comparison group and found a surprising low dementia rate of 1 %, suggesting offending was less related to cognition and more to personality factors [58]. Similarly, in comparing 50 elderly sexual and non-sexual offenders, again frontal lobe dysfunction was apparently normal [59].…”
Section: Aging and Sexual Offendingmentioning
confidence: 98%
“…In 2000, one-third of adults aged 60 years or over received into prison under immediate sentence in England and Wales had been convicted of a sexual offence (compared with about 3% for the prison population as a whole). About half of older male prisoners under sentence are sex offenders (Fazel et al 2002).…”
Section: The Social Production Of Elder Imprisonmentmentioning
confidence: 99%
“…Rapists and violent offenders were more commonly intoxicated during the commission of the offence. Compared with violent offenders, sex offenders exhibited more schizoid, obsessive-compulsive and avoidant traits, and fewer antisocial traits (Fazel et al, 2002). Chantry and Craig (1994) reported that sexual offenders tended to be more passive, submissive and lacking in initiative than other offender groups, and aggressive offenders displayed more ego-centred, grandiose and narcissistic traits than did sexual offenders.…”
Section: Introductionmentioning
confidence: 97%